2017
DOI: 10.1111/os.12344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Asymmetric Tension on Biomechanics and Metabolism of Vertebral Epiphyseal Plate in a Rodent Model of Scoliosis

Abstract: In this study, asymmetric tension contributed to asymmetry in protein expression and bone quality on vertebral epiphyseal plates, ultimately resulting in asymmetry of anatomy. In addition, asymmetry of anatomy aggravated asymmetric tension. It is the first study to show that there is an asymmetrical vicious circle in IS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Our results suggest that the convex side has a lower bone volume than the concave side which is consistent with Wolff’s law, that is, bone formation will increase in areas of compression and decrease in areas of tension. Although previous studies have reported that the convex side shows a higher bone volume than the concave side in a rodent model of scoliosis [41], we assumed that this discrepancy might be because animal models cannot fully reflect the pathophysiology of AIS. In addition, the qPCR, western blotting and immunochemistry also confirmed the imbalance between concave and convex side.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the convex side has a lower bone volume than the concave side which is consistent with Wolff’s law, that is, bone formation will increase in areas of compression and decrease in areas of tension. Although previous studies have reported that the convex side shows a higher bone volume than the concave side in a rodent model of scoliosis [41], we assumed that this discrepancy might be because animal models cannot fully reflect the pathophysiology of AIS. In addition, the qPCR, western blotting and immunochemistry also confirmed the imbalance between concave and convex side.…”
Section: Discussionmentioning
confidence: 99%
“…AIS may be caused by abnormal cartilage development. Some researchers found that the imbalanced expression of sox9, collagen II, collagen X, and aggrecan on both sides of the spine may be the cause of scoliosis [46, 47]. Cartilage oligomeric matrix protein (COMP) played a role in maintaining the structural integrity of cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…PVM is vital for the stability and functional movement of the spinal column; tension imbalance is a key factor in the initiating or maintaining scoliotic curvature by muscle contraction [33]. The stiffness of concave PVM was greater than that on the convex side in IS patients.…”
Section: Biomed Research Internationalmentioning
confidence: 92%